Representaciones sociales presentes en la construcción de la identidad personal de cuatro (4) estudiantes de la universidad Antonio Nariño sede Roldanillo - Gómez Caviedes, María Fernanda (Universidad Antonio Nariño, 2023)
The aim of this research is to understand the social representations present in the construction of the personal identity of the students of the Antonio Nariño University, Roldanillo campus, from the narratives that emerge from the social, cultural, family, and technological aspects. This research has a qualitative approach, the type of research is of phenomenological order since, as referred by Borda (2013) phenomenology tries to understand society from the perspective of the subject-actor, of the one who lives it, since it is considered that reality does not exist without its authors, as it is that which is perceived and understood by people. The results allowed to establish four (4) emerging categories for the development of the data analysis: 1) experiences lived from the role of the SOCIAL to build the concept of personal identity; 2) influence of CULTURE to build the concept of identity; 3) roles and relationships in the construction of identity from the FAMILY area; 4) attitude and relationship in the development of identity when TECHNOLOGY influences.